ANALISIS USAHA RUMAH MAKAN SI BOLANG DAN KUALITAS LAYANAN TERHADAP KONSUMEN DI KECAMATAN BONTANG UTARA KOTA BONTANG - Salmah Pujiastuti; Dayang Diah Fidhiani; Oon Darmansyah (2339-1324, 2020)
This research aims to know the cost, admission, profit, RCR, payback period and analysis of Break Even Point (BEP) from Si Bolang Restaurant and to know the consumers’ satisfaction level towards the service quality provided in Si Bolang Restaurant. The result of this research shows that Si Bolang restaurant business spends total of Rp. 77.898.256/month with admission of Rp. 100.315.000/month, thus the profit is as much as Rp. 22.416.744/month. The RCR is as much as 1,29 which means that Si Bolang restaurant business is profitable and feasible to be developed with investment capital payback period is 1 year 8 months 2 weeks 1 day. As a whole, BEP experiences profit with BEP of production as much as 1.839 portion/month < 2.400 portion/month, BEP of price is as much as Rp. 353.553 < Rp. 460.000 and BEP of Sale is as much as Rp. 48.157.675 < Rp. 100.315.000. The analysis of consumers’ satisfaction for the service quality provided by Si Bolang Restaurant in each dimension including tangible, reliability, responsiveness, assurance and emphaty as a whole obtained mean gap score of 0,25 which indicates that the consumers are very satisfied with the service quality provided by Si Bolang Restaurant. Keyword: The Analysis of Business, Service Quality, Consumers and Si Bolang Restaurant